Living with Kallmann Syndrome – Analysis of Subjective Experience Reports from Women - Hofmann, J.; Watzlawik, M.; Richter-Appelt, H. (Geburtshilfe und Frauenheilkunde, 2013)
Five women were questioned on their experiences with Kallmann Syndrome (KS) in thematically focused, open interviews. This investigation complements the study of the experiences of men with KS 1. The results show that the consequences and pressures of KS extend beyond the somato-medical field and that those affected are also burdened by mental and psycho-social impacts. The pressures experienced by those affected include a distorted body image resulting from the lack of physical development, which in turn leads to difficulties in developing a healthy feeling of self-worth. Furthermore, particular attention should be paid to the influence of hormone therapy on mood and libido during medical treatment. Some of the affected women reported experiencing depressive moods and low libido, and pressures in their relationship associated with this. The affected women wanted KS to be viewed as a whole in order to achieve better handling. In particular, attentive handling of issues relating to fertility was important to them. Additional relevant support included offers of confidential discussions, and offers of psychotherapy and, where required, sex education or sex therapy.
Keywords: adolescence; hormone replacement; puberty; disturbance of puberty